Prevalence of Anaplasma marginale, Babesia bovis, and Babesia bigemina in cattle in the Campos de Lages region, Santa Catarina state, Brazil, estimated by multiplex-PCR - Vieira L.L.* (2019)
© 2019 The AuthorsThis study aimed to determine the prevalence of three common hemoparasites (Anaplasma marginale, Babesia bovis and Babesia bigemina) in cattle from 16 counties in the Campos de Lages region, Santa Catarina state, Brazil, and the factors affecting disease occurrence. The study population consisted of 257 clinically healthy animals from 21 rural farms. Bovine blood samples were collected by jugular venipuncture. DNA was extracted from whole blood by the phenol/ chloroform method. Genomic DNA extracted from blood samples was subjected to Multiplex PCR for screening of B. bovis, B. bigemina, and A. marginale using specific primers. Prevalences of A. marginale, B. bigemina, and B. bovis were 27%, 16%, and 29%, respectively. Mixed infection was observed in 17.5% of samples. The most frequent was Babesia bovis and Babesia bigemina in 6.62% of samples. A. marginale infection rates were statistically correlated with age groups of cattle. The infections detected in the study population were considered to be subclinical, based on the presence pathogen DNA and absence of clinical symptoms. Seasonality of the pathogens resulted in various degrees of infection, related to the age of the animals and the season. The Campos de Lages region is characterized by enzootic instability for these pathogens because of its climatic and geographic features.